Young Generation’s Investment Motivation: Insights from a Self-Determination Theory Perspective - Ilham Abu; Mahmudatus Sholihah; Wahyudin (Fundamental and Applied Management Journal, 2024)
This study aims to understand investment motivation among students in Makassar using the Self-Determination Theory (SDT) framework. Data were collected from students through an online questionnaire and analyzed using SPSS software. The findings indicate that students' investment motivation is influenced by several key factors, including autonomous motivation, competence, social relatedness, intrinsic motivation, and commitment. The results highlight that students have a strong desire to independently manage their investment activities, feel confident in their ability to understand and engage in investment, and benefit from the support of peers, family, and community. Intrinsic motivation plays a significant role, reflecting personal satisfaction and interest in investment, while high levels of commitment suggest a strong dedication to maintaining their investment activities. Overall, the study reveals that students in Makassar exhibit a high level of investment motivation, driven by the need for autonomy, competence, and social connections. The research underscores the importance of financial literacy and social support in shaping students' investment motivation. Educational institutions and financial organizations are encouraged to collaborate in enhancing financial literacy and providing educational programs that support students' investment motivation.